WHAT ARE BEHAVIOR OF WOMEN THAT RELATED TO OBESITY AND METABOLIC SYNDROME : A BIBLIOMETRIC ANALYSIS - Ayusari, Amelya Augusthina; Lanti, Yulia; Wiboworini, Budiyanti (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Background: Women are susceptible to have obesity and metabolic syndrome (MS), Inappropriate attitudes and behaviors can exacerbate obesity and MS.Objective: This study aims to determine research trends in the Scopus database regarding behaviors related to obesity and MS in women.Methods: The study was started collecting some articles from Scopus database using the spesific keywords, then the data was analyzed bibliometrically using VOSviewer 1.6.18 software to visualize the network or the relationship between topics as well as visualize the distribution of the year when the topic was studied.Results: About 772 articles were analyzed, behaviors related to obesity and MS that have been studied in Scopus database during 2013-2022 period were diet, feeding behavior, drinking behavior and smoking. Then, 2014 was the year when this topic most frequently studied.Conclusion: Bibliometrically from scopus database, behavior of women that related to obesity and MS are diet, feeding behavior, drinking behavior and smoking.